The Environmental CSR Awareness-Satisfaction Paradox: Understanding Customer Perceptions and Behavioural Intentions in Hospitality Services - AHMAD, Huzaifa (Journal of Environmental Management and Tourism; Vol 16 No 3 (2025): JEMT, Volume XVI, Issue 3(79), Fall 2025DO - 10.14505/jemt.v16.3(79).03, 2025)
This study explores a paradoxical relationship between environmental CSR awareness and customer satisfaction within the Malaysian hospitality sector. The research uncovers how high CSR awareness can negatively influence satisfaction while positively impacting behavioural intentions. Data was collected via survey from 400 hospitality customers and analyzed using Random Forest, K-means clustering, and regression models to examine the relationships between environmental CSR awareness, customer satisfaction, and behavioural intentions. The analysis reveals that increased environmental CSR awareness correlates negatively with customer satisfaction but positively with behavioural intentions like willingness to pay more. Four distinct customer segments emerged, showing varying perceptions and satisfaction patterns. This paper challenges the conventional belief that CSR always enhances satisfaction, offering empirical evidence of the Environmental CSR Awareness-Satisfaction Paradox. The study provides a new lens to understand complex customer psychology in sustainable hospitality. The findings are limited to the hospitality industry in Malaysia and may not generalize across regions or sectors. Understanding this paradox helps hospitality businesses better strategize CSR communication and customer engagement. Insights contribute to policymaking and service design promoting sustainable consumer behaviour.